Managing elite sport systems (Routledge Research in Sport Business and Management, 2015)
Content Part 1: How different systems work 1. Systems and the development of elite athletes 2. `Big brother` and caring sister: Performance management and the athlete`s entourage ' 3. Modernisation and elite sport development in England and the United Kingdom: talent identification and coach development 4. The ecology of talent development in the Nordic elite sport model 5. Resources and Capabilities? Developing Malaysian National Sport Associations Part 2: Delivering athlete support 6. Managing core processes in elite athlete development: Norwegian cross country skiing 7. Talent identification and development in Germany - state of play and current tasks 8. Training environments - more than bricks and mortar 9. Integrating the micro and meso-level approaches to athlete development and success 10. Performance leadership and management in elite sport: Current status and future directions 11. Managing heterogeneity and complexity